LEGAL BASIS OF THE INCOME TAX OF INDIVIDUALS - Скупейко, Василь; Вознюк, Олена; Лихолат, Світлана (Socio-economic relations in the digital society, 2019)
The article emphasizes that the imperfection and uncertainty of taxlegislation are reflected primarily in the content of the rights and freedoms of citizens of the country. Accordingly, effective management of the economy, taxregulation can be implemented only in the unification and interaction of interests of the individual and the state, respecting the principle of mutual responsibility. The article deals with the legal bases of taxation of personal income. It is determined that the Tax Code of Ukraine does not provide an optimal solution to the issues of taxation of income and levies on the income of individuals, since the main taxburden on the personal income taxlieson citizens who do not have high income. The main drawback of theTax Code is the largest number of personal income taxes in the world, which complicates the transparency of taxes and their accrual to both taxpayers and taxspecialists. It is determined that the personal income tax applies not only to specialists but also to ordinary citizens. Therefore, it is very important to observe the principles of accessibility and simplicity of taxation. In order to simplify the administration of taxes on personal income, it is proposed to group the components of the taxpayer’s total income according to the relevant criteria. Due to the inability to repay the resident due to the lack of local tax fundsatthebeginningof the year, it would be advisable to take into account the tax rebate before the taxpayer’s taxliability, reducing it by the amount of taxrebate provided on the basis of the documents submitted. According to the results of researches of scientific financial and legal sources of the modern period and analysis of the tax legislation of Ukraine, conclusions and proposals on improvement of the personal income tax have been made, in particular in the part of revision of the main provisions of the Tax Code on the number of taxes and taxsystem that meets international standards